Determining thermodynamic parameters of mt2+ ion binding to polynucleotides being in different conformations, by "phase diagrams" method - Sorokin, V. A.; Babenko, V. I.; Usenko, E. L.; Zhigalova, N. N. (Biophysical Bulletin, 2009)
Thermodynamic parameters (association constants K, stoichiometry of complexes n) of three (polyU-polyA-polyU=A2U) -, double (polyA-polyU=AU) - and single-stranded (polyA, polyU) polynucleotide binding to Ni2+ ions were calculated. In addition, enthalpies (ΔH) for A2U—>AU+polyU transition (3—>2 transition) and AU—>polyA+polyU transition (2—>1 transition) were determined. In both cases, the "clips" theory and phase diagram for A2U complexes with the above ions were applied. Except for the case with AU, Ni2+ ion effect on temperatures of corresponding transitions is noticeably conditioned with their interactions with negative charges on the surface of three- and single-stranded polynucleotides. Based on the theoretical analysis of phase diagrams for polynucleotide metal complexes, the comparison of the calculated and experimental data showed that the method for determining K, n, and ΔH is an ideal alternative to the direct experimental determination of these parameters